2021
DOI: 10.37034/jidt.v3i3.116
|View full text |Cite
|
Sign up to set email alerts
|

Prediksi dan Klasifikasi Buku Menggunakan Metode Backpropagation

Abstract: Students of SMP Negeri 2 Lengayang have different interests in determining the books they are interested in, so that the library often has difficulty determining the books that are most entered by students, this is because they have not used the right system in determining the type and number of books, only based on the estimated number. Students and subjects only, as a result school students stock books of the books they want to borrow. Based on the above, a method is needed to predict and classify the amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…90% of the training data can provide enough data to train a classification model. The more data used for training, the better the model will likely learn the patterns in that data (Rahmawati 2019). Meanwhile, the test data in this study used 768 data, as shown inTable 4.…”
Section: Table 1 Research Data After Transformation To Binary Formmentioning
confidence: 99%
See 1 more Smart Citation
“…90% of the training data can provide enough data to train a classification model. The more data used for training, the better the model will likely learn the patterns in that data (Rahmawati 2019). Meanwhile, the test data in this study used 768 data, as shown inTable 4.…”
Section: Table 1 Research Data After Transformation To Binary Formmentioning
confidence: 99%
“…This research aims to utilize student data at universities to classify student dropouts using the learning vector quantization (LVQ) algorithm. LVQ is one of the classification methods of artificial neural networks that applies the principle of competition (Rahmawati 2019). LVQ is a grouping method where the labels for each class have been determined (supervised learning).…”
Section: Introductionmentioning
confidence: 99%
“…Jumlah epoch pelatihan adalah 4595 dan pencapaian MSE (Mean Squared Error) pada pengujian adalah 0,001 serta hasil akurasi yang didapatkan adalah 99,99900000% [11]. Selain itu juga penelitian tentang prediksi dan klasifikasi buku menggunakan metode backpropagation [12]. Penelitian lainnya yang melibatkan Algoritma Backpropagation adalah dalam menentukan klasifikasi 5 varietas padi melalui citra scan laser tiga dimensi (3D) [13], penentuan tingkat kematangan sawit pada 116 citra tandan buah segar [14].…”
Section: Pendahuluanunclassified